2022
DOI: 10.1182/bloodadvances.2022008086
|View full text |Cite
|
Sign up to set email alerts
|

ICH in primary or metastatic brain cancer patients with or without anticoagulant treatment: a systematic review and meta-analysis

Abstract: Anticoagulant treatment in patients with primary and metastatic brain cancer is a concern due to risk of intracranial hemorrhage (ICH). We performed a systematic review and meta-analysis to evaluate the risk of ICH in patients with primary or metastatic brain cancer treated or not with anticoagulants. Articles on ICH in patients with primary or metastatic brain cancer treated or not with anticoagulants published up to September 2021 were identified by searching PUBMED, EMBASE and CENTRAL.The primary outcome of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 45 publications
0
13
1
Order By: Relevance
“…Many studies find that anticoagulation for VTE in patients with GBM substantially increases the rate of ICH compared with patients with GBM with or without VTE, who did not receive anticoagulation. [16][17][18][19] Alternatively, other retrospective studies fail to show an increased risk of symptomatic ICH in LMWH-treated patients with glioma. 20,21 A retrospective matched cohort study of 220 patients with glioma found a cumulative 1-year risk of symptomatic ICH of 17% in patients receiving LMWH for VTE versus 13% for matched patients without VTE and no median survival difference.…”
Section: Comparing Doacs With Low-molecular-weight Heparin and Warfar...mentioning
confidence: 99%
See 2 more Smart Citations
“…Many studies find that anticoagulation for VTE in patients with GBM substantially increases the rate of ICH compared with patients with GBM with or without VTE, who did not receive anticoagulation. [16][17][18][19] Alternatively, other retrospective studies fail to show an increased risk of symptomatic ICH in LMWH-treated patients with glioma. 20,21 A retrospective matched cohort study of 220 patients with glioma found a cumulative 1-year risk of symptomatic ICH of 17% in patients receiving LMWH for VTE versus 13% for matched patients without VTE and no median survival difference.…”
Section: Comparing Doacs With Low-molecular-weight Heparin and Warfar...mentioning
confidence: 99%
“…A systematic review of 3893 patients found that ICH rates were much higher in BM compared with primary BTs (13% vs. 6.4%, respectively). 19 Some report ICH rates as much as 20% in metastatic cancer patients. 47 Counterintuitively, studies report no increase in ICH for metastatic patients with BT treated with LMWH versus no anticoagulation, to a 3-fold increase ICH risk in primary patients with BT receiving LMWH versus no anticoagulation.…”
Section: Safety Of Doac Use In Primary Bts Compared With Brain Metast...mentioning
confidence: 99%
See 1 more Smart Citation
“…Giustozzi et al 1 recently published a systematic review and meta-analysis that investigated intracranial hemorrhage (ICH) in patients with primary or metastatic brain cancer managed with or without anticoagulants. The analysis included 30 retrospective studies and concluded that (1) the rate of ICH and major ICH is higher in patients with metastatic brain cancer than in those with primary brain cancer (all ICH, 13% vs 6.4%; major ICH, 15.4% vs 3.9%), (2) anticoagulation is associated with an increased risk of ICH and major ICH in patients with primary brain cancer but not in those with metastatic brain cancer, and (3) the risk of ICH is a third lower in patients treated with a direct oral anticoagulant (DOAC) than in those treated with low-molecular-weight heparin (LMWH).…”
mentioning
confidence: 99%
“…We wish to thank Buka and Sutton for their comments on our recently published article. 1 Among the results of our meta-analysis of patients with primary or metastatic brain cancer and VTE, the authors focused their attention on the lower risk of intracranial bleeding (ICH) in patients treated with direct oral anticoagulants (DOACs) than that in those receiving low-molecular weight heparin (LMWH) and advice caution for implementing this finding in the clinical practice. The authors state that these conclusions are driven mainly by Carney’s study, which has several limitations including (1) the retrospective design, (2) the patient population, and (3) the potential selection bias.…”
mentioning
confidence: 99%